New Medical Device and Therapeutic Approvals in Otolaryngology: State of the Art Review 2020 - Michael J. Brenner MD (SAGE Publishing, 2021)
Objectives To evaluate new drugs and devices relevant to otolaryngology–head and neck surgery that were approved by the US Food and Drug Administration (FDA) in 2020. Data Sources Publicly available device and therapeutic approvals from ENT (ear, nose, and throat), anesthesia, neurology (neurosurgery), and plastic and general surgery FDA committees. Review Methods Members of the American Academy of Otolaryngology–Head and Neck Surgery’s Medical Devices and Drugs Committee reviewed new therapeutics and medical devices from a query of the FDA’s device and therapeutic approvals. Two independent reviewers assessed the drug’s or device’s relevance to otolaryngology, classified to subspecialty field, with a critical review of available scientific literature. Conclusions The Medical Devices and Drugs Committee reviewed 53 new therapeutics and 1094 devices (89 ENT, 140 anesthesia, 511 plastic and general surgery, and 354 neurology) approved in 2020. Ten drugs and 17 devices were considered relevant to the otolaryngology community. Rhinology saw significant improvements around image guidance systems; indications for cochlear implantation expanded; several new monoclonal therapeutics were added to head and neck oncology’s armamentarium; and several new approvals appeared for facial plastics surgery, pediatric otolaryngology, and comprehensive otolaryngology. Implications for Practice New technologies and pharmaceuticals offer the promise of improving how we care for otolaryngology patients. However, judicious introduction of innovations into practice requires a nuanced understanding of safety, advantages, and limitations. Working knowledge of new drugs and medical devices approved for the market helps clinicians tailor patient care accordingly.